On the calculation of the gauge volume size for energy-dispersive X-ray diffraction - Rowles, Matthew (Blackwell Publishing, 2011)
Equations for the calculation of the dimensions of a gauge volume, also known as the active volume or diffraction lozenge, in an energy-dispersive diffraction experiment where the detector is collimated by two ideal slits have been developed. Equations are given for equatorially divergent and parallel incident X-ray beams, assuming negligible axial divergence